Silver nanoparticles: From in vitro green synthesis to in vivo biological effects in plants - Na Zhang; Juzhi Sun; Liyan Yin; Junli Liu; Chunli Chen (Advanced Agrochem, 2023)
Silver nanoparticles (AgNPs) are extensively utilized in industrial, biotechnological and medical fields because of their specific physical and chemical properties, which shown small size effects, surface and interface effects, quantum scale effects. Inevitably, wastewater containing AgNPs is leached into the soil. AgNPs in soil may be absorbed by plant roots and they affect plant growth. Understanding the complex interactions between AgNPs and plants is of crucial significance since plants are essential to the ecological environment as key players in ecosystems. Most previous reports have focused on AgNP phytotoxicity rather than positive effects in the plant field. This article reviews recent studies on the important aspects about nanoparticles including the green synthesis, absorption, migration, accumulation, biotransformation, biological effects, and the underlying molecular mechanisms of AgNPs affecting plants. We provide insights into the interactions between AgNPs and plants, helping to further understand AgNP-related effects and biosafety in agricultural production, as well as the practical application of various nanomaterials in agriculture.